Menstrual hygiene practice and school absenteeism among rural adolescent girl of Raskot, Kalikot. - Bhat,Deepmala Rana (2018)
ABSTRACT: Menstruation is a part of female reproductive cycle that starts when girls become sexually mature at the time of puberty. It is a phenomenon unique to the females. During menstrual period a woman bleeds from her uterus via vagina.This study was doneto assess the menstrual hygiene practice and school absenteeism among the rural school going adolescent girls.A descriptive study was done among three hundred and twenty-one female adolescents of Badhimalika higher secondary school, Malika secondary school, Motiram higher secondary school and Kalashila secondary school, Raskot, where data were collected from the adolescents meeting the inclusion criteria.It was found that majority of student's menstrual hygiene practice was not good i.e. 86.9% and only 13.1% of respondent's hygiene practice was good. Majority of respondents (96 %) used clean cloth (piece of cloth) during their menstruation cycle, whereas only 4% (13) of respondents used sanitary pad. Almost every adolescent girl i.e. 98.8 % (317) practiced any restrictions during menstruation. About 9.3% respondent did not attend school during menstrual cycle. And the reasons for not attending school, was due to illness related to menstruation such as stomachache, pain in back, heavy bleeding etc. About one in four respondent were absent in school during their last menstruation. The study revealed the fact that among the adolescent girls of the study area, the overall menstrual hygiene practice was found to be poor and the various beliefs were found to be inappropriate. Separate functioning sanitary facilities for girl students was not available in schools due to which sanitation during menstruation was not maintained. Although there was separate sanitary facilities for girls and boys in one school among four schools, those facilities were locked by school and students preferred to use open areas.There was significant association between age of respondents and menstrual hygiene practice. Similarly there was association between type of family and school absenteeism during last menstruation. The study findings shows that there is the need to encourage safe and hygienic practices among the rural adolescent girls and bring them out of traditional beliefs, misconceptions and restrictions regarding menstruation.